FOOD POISONING AMONG CHILDREN AND ITS PREVENTION - Tursunkulova D.Sh., Tukhtarov B.E. (Central Asian Journal of Medicine, 2025)
Food poisoning is a serious health problem that occurs when harmful microorganisms, chemicals, or other toxic elements enter the human body through food. This condition is especially common among children, since their immune systems are weaker than those of adults and the body's defense mechanisms are not fully developed. Therefore, food poisoning is one of the most common problems in children, and this condition can cause significant harm to children's health. Food poisoning can lead not only to a deterioration in physical condition, but also to life-threatening complications. Therefore, it is very important to study this issue in depth, to know its causes, symptoms, and preventive measures.